Metabolic Changes in Avena sativa Crowns Recovering from Freezing - Henson, Cynthia A. (Public Library of Science, 2014)
Extensive research has been conducted on cold acclimation and freezing tolerance of fall-sown cereal plants due to their economic importance; however, little has been reported on the biochemical changes occurring over time after the freezing conditions are replaced by conditions favorable for recovery and growth such as would occur during spring. In this study, GC-MS was used to detect metabolic changes in the overwintering crown tissue of oat (Avena sativa L.) during a fourteen day time-course after freezing. Metabolomic analysis revealed increases in most amino acids, particularly proline, 5-oxoproline and arginine, which increased greatly in crowns that were frozen compared to controls and correlated very significantly with days after freezing. In contrast, sugar and sugar related metabolites were little changed by freezing, except sucrose and fructose which decreased dramatically. In frozen tissue all TCA cycle metabolites, especially citrate and malate, decreased in relation to unfrozen tissue. Alterations in some amino acid pools after freezing were similar to those observed in cold acclimation whereas most changes in sugar pools after freezing were not. These similarities and differences suggest that there are common as well as unique genetic mechanisms between these two environmental conditions that are crucial to the winter survival of plants.